Empowering Waste Management by Establishing a Waste Corner to Become a Healthy School: Pemberdayaan Pengelolaan Sampah dengan Pembentukan Pojok Sampah Guna Menjadi Sekolah Sehat - Jayadi, Yusma Indah; Maharani, Widia; Nurlita, Nurlita; Wijaya, Dian Rezki (Yayasan Ahmar Cendekia Indonesia, 2023)
Waste is often defined as goods or materials that are considered useless so that they never get good management through the recycling process. Human quality is a major issue and has an important role in management efforts. Empowerment programs in the environment school as a source of environmental learning through waste management is one of the efforts that can be given to students to increase environmental awareness. This empowerment program aims to increase the knowledge and awareness of the school community in waste management correctly and properly. This Empowerment Program was conducted at SJHS 8 Makassar by making waste corner and forming waste corner cadres through the approach of Participatory Learning and Action (PAL). This program involved 15 students who became cadres of the waste corner and 45 students who were given education by the waste corner cadres. As a result of this empowerment, a waste corner was formed and 15 waste corner cadres were selected. Giving training to waste corner cadres was considered effective because there was an increase in knowledge before and after the training, from 12.67 to 18.87. Besides that, education by waste corner cadres to 45 students of SJHS 8 Makassar showed an increase in knowledge, from 13.22 to 17.91. The result of the paired t-test showed a significance value of p = 0.000 (p < 0.05) so it could be concluded that there is a different level of knowledge of cadres and students before and after training/education on waste management. Community empowerment through the establishment of waste corners and waste corner cadres as well as providing training/education related to waste management has a significant effect on the level of knowledge about waste management. Therefore, it is necessary to provide continuous socialization to increase the interest and participation of the school community in waste management. Abstrak Sampah sering kali diartikan sebagai barang atau material yang dianggap tidak berguna sehingga tidak pernah mendapatkan pengelolaan yang baik melalui proses daur ulang. Kualitas manusia menjadi isu utama dan memiliki peran penting dalam upaya pengelolaannya. Program pemberdayaan di lingkungan sekolah sebagai sumber belajar lingkungan melalui pengelolaan sampah merupakan salah satu upaya yang dapat diberikan kepada siswa untuk meningkatkan kepedulian terhadap lingkungan. Program pemberdayaan ini bertujuan untuk meningkatkan pengetahuan dan kesadaran warga sekolah dalam pengelolaan sampah dengan baik dan benar. Program Pemberdayaan ini dilakukan di SJHS 8 Makassar dengan membuat pojok sampah dan membentuk kader-kader pojok sampah melalui pendekatan Participatory Learning and Action (PAL). Program ini melibatkan 15 siswa yang menjadi kader pojok sampah dan 45 siswa yang diberikan edukasi oleh kader pojok sampah. Hasil dari pemberdayaan ini adalah terbentuknya pojok sampah dan terpilihnya 15 orang kader pojok sampah. Pemberian pelatihan kepada kader pojok sampah dinilai efektif karena terjadi peningkatan pengetahuan sebelum dan sesudah pelatihan, yaitu dari 12,67 menjadi 18,87. Selain itu, edukasi yang dilakukan oleh kader pojok sampah kepada 45 siswa SJHS 8 Makassar menunjukkan adanya peningkatan pengetahuan dari 13,22 menjadi 17,91. Hasil uji t berpasangan menunjukkan nilai signifikansi p = 0,000 (p < 0,05) sehingga dapat disimpulkan bahwa terdapat perbedaan tingkat pengetahuan kader dan siswa sebelum dan sesudah pelatihan/edukasi pengelolaan sampah. Pemberdayaan masyarakat melalui pembentukan pojok sampah dan kader pojok sampah serta pemberian pelatihan/edukasi terkait pengelolaan sampah memberikan pengaruh yang signifikan terhadap tingkat pengetahuan tentang pengelolaan sampah. Oleh karena itu, perlu dilakukan sosialisasi secara terus menerus untuk meningkatkan minat dan partisipasi warga sekolah dalam pengelolaan sampah.